If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -6 = 3(x + 9) Reorder the terms: -6 + 12x = 3(x + 9) Reorder the terms: -6 + 12x = 3(9 + x) -6 + 12x = (9 * 3 + x * 3) -6 + 12x = (27 + 3x) Solving -6 + 12x = 27 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -6 + 12x + -3x = 27 + 3x + -3x Combine like terms: 12x + -3x = 9x -6 + 9x = 27 + 3x + -3x Combine like terms: 3x + -3x = 0 -6 + 9x = 27 + 0 -6 + 9x = 27 Add '6' to each side of the equation. -6 + 6 + 9x = 27 + 6 Combine like terms: -6 + 6 = 0 0 + 9x = 27 + 6 9x = 27 + 6 Combine like terms: 27 + 6 = 33 9x = 33 Divide each side by '9'. x = 3.666666667 Simplifying x = 3.666666667
| 13(x-2)=8x-6 | | 123456790*23456789+1234567890= | | 10=-30x+10 | | (w)=0 | | .25(12+x)=.6+.35x | | 9p^2-12p=0 | | (w)=1 | | (w)=-1 | | -9n^2-9=315 | | 5+6x+25=180 | | (w)=-2 | | 8-10p=88 | | 4c-10=-9+3c | | (7y+2)(y-5)= | | 8x(8+6x)=20 | | .25(12x)=.6+.35x | | -2(x-4)=-6(2+x) | | 5(x+1)+51=-2x | | 4x+14=6x-26 | | 2m+7(m-1)=-21-5m | | 5+6y=5y+10 | | -abx^2+bcx+1=0 | | 5+y^2+7=3 | | 15w-22=-111 | | 8v+4=2v-8 | | 4(x-4)+2x=4x-6 | | (6y+5)(y-2)= | | 13x+7=6x+14 | | -3+7q=-7+9q | | -(1+6m)+6m=-11+3(r-7) | | Y=(5t^2)*(5t^3) | | -2(3)(-5)= |